En jämförande studie av stubbens skottskjutning efter röjning med kedjeröjsåg kontra klingröjsåg - Hassel, Johan (SLU/School for Forest Management, 2018)
In the young forests of Sweden the birch covers 30 percent of the standing volume and is a big competitor to the spruce- and pine seedlings. The dominating method to handle naturally rejuvenated birch in the young forest is to use a brush cutter. From a cut off birch stump grows sprouts that can grow very fast and a second and even a third cleaning can be necessary.